Advances in Energy Harvesting Methods - Elvin, Niell; Erturk, Alper (Springer New York : Imprint: Springer, 2013)
Advances in Energy Harvesting Methods presents a state-of-the-art understanding of diverse aspects of energy harvesting with a focus on: broadband energy conversion, new concepts in electronic circuits, and novel materials. This book covers recent advances in energy harvesting using different transduction mechanisms; these include methods of performance enhancement using nonlinear effects, non-harmonic forms of excitation and non-resonant energy harvesting, fluidic energy harvesting, and advances in both low-power electronics as well as  material science. The contributors include a brief literature review of prior research with each chapter for further reference. This book covers: Multiphysics problems such as fluidic energy harvesting Nonlinear effects for performance enhancement, for example, broadband energy harvesting Examples of realistic problems of energy harvesting, such as from random ambient vibration Recent advances in low-power circuitry, such as efforts in ultra-low power analog circuit design as well as recent advances in novel energy harvesting materials and fabrication techniques Advances in Energy Harvesting Methods is an ideal book for students, faculty, and practicing engineers in mechanical, electrical, civil, and aerospace engineering as well as material science.    .